2018
DOI: 10.15446/abc.v23n3.67245
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a polychaete community in a mangrove in the northern coast of Brazil

Abstract: Los poliquetos desempeñan un importante papel en la estructura y funcionamiento de las comunidades bentónicas de manglares; sin embargo, el conocimiento sobre estos organismos permanece escaso en la costa amazónica de Maranhão, Brasil. Este estudio analizó los aspectos ecológicos de la comunidad de poliquetos del manglar Quebra Pote, Estado de Maranhão. Se realizaron cuatro recolectas durante el período de secas y lluvias, entre noviembre 2013 y julio 2014, se delimitó un transecto de 100 metros de longitud, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…In the survey area, the average density of polychaetes decreased after the end of the rainy season. Some previous studies have reported similar changes [47,48]. This shift shows that a large amount of rainfall affected the benthic ecosystem, which may lead to the development of a new benthic environment [49].…”
Section: Discussionsupporting
confidence: 61%
“…In the survey area, the average density of polychaetes decreased after the end of the rainy season. Some previous studies have reported similar changes [47,48]. This shift shows that a large amount of rainfall affected the benthic ecosystem, which may lead to the development of a new benthic environment [49].…”
Section: Discussionsupporting
confidence: 61%
“…The results point localizations with high organic matter content and low density and richness of lumbrinerid, nereidid, and spionid Polychaeta, comparing with other beaches in the region (Coelho- Costa 2007, Feres et al 2008, Cutrim 2017, Tavares-Cutrim et al 2018. The degree of sediment Wentworth (1992) classification and in the degree of selection from Folk and Ward (1957).…”
Section: Discussionmentioning
confidence: 84%
“…Additionally, they are eaten by seabirds, fish, and crustaceans with commercial value. As a result of their abundance, diverse feeding habits, occupation of niches, and the relationship to different sediment types, they play an important role in the structure and functioning of benthic communities [8]. Also, polychaetes are active participants in a variety of marine ecological processes, including bioturbation, nutrient cycling, secondary production, and energy flow [9,10].…”
Section: Introductionmentioning
confidence: 99%